Nurses’ experiences of serving as a communication guide and supporting the implementation of a communication intervention in the intensive care unit - Anna Holm; Veronika Karlsson; Pia Dreyer (International Journal of Qualitative Studies on Health & Well-Being, 2021)
Purpose : To explore the experience of serving as a nurse communication guide, supporting the bottom-up implementation of a multi-component communication intervention prototype in the intensive care unit. Methods : The overall frame was Complex Interventions, and the study was conducted within the phenomenological-hermeneutic tradition. Semi-structured telephone interviews were conducted with eight nurse communication guides. Data were analysed using a Ricoeur-inspired interpretation method. Results : Two main themes emerged: 1) “The communication intervention components provided overview, a conceptual framework, awareness and room for reflection” and 2) “Being a communication guide illuminated the barriers and challenges of implementation”. Furthermore, a comprehensive understanding was established that illuminated experiences throughout the analysis: “An ICU communication intervention has to be adaptable to the specific situation and the double need for individualization but also provide overall guidance”. Conclusion : Findings showed that as communication is inherent to all human beings, it can be difficult to change the communication behaviour of nurses. Therefore, a communication intervention in the intensive care unit must be sensitive to the nurse communication guides’ individual communication style. Furthermore, a communication intervention should provide nurse communication guides with overall guidance while at the same time remaining adaptable to the needs of each specific situation.